White Christmas from the Motion Picture Irving Berlin's "Holiday Inn" - Berlin, Irving 1888-1989 (Irving Berlin Music Company, 2011)
Enhance any holiday concert with Mark's smooth light bossa treatment of one of Irving Berlin's most popular songs. Scored for 6 horns, this arrangement will sound great with limited amount of rehearsal time. - Publisher
Level: 3-4
Song from the motion picture "Holiday Inn.
Originally published in ©1940 (Renewed) Irving Berlin
Parts for: alto sax, tenor sax, baritone sax, trumpet (2), trombone, guitar, piano, bass, drums. Includes Solo sheets for C treble clef and B clef instruments, B ♭ and E ♭ instruments. Alternative alto sax (substitute for tpt.2), alternative tenor sax (substitute for tbn.), alternative trombone (substitute for bari. sax)
Keywords: Band music, Arranged; Band music, Arranged / Parts; Jazz / Scores and parts; Big band music / Scores and parts; Harmonie (Orchestre), Musique d', arr; Harmonie (Orchestre), Musique d', arr / Parties